Innovation in Multilateralism
XXVI, 344 p.
Keywords: The chapters in this volume identify and assess the political process and bases of support for multilateralism in terms of the shifting power relations in world politics, institutional innovations in the United Nations and non-UN multilateralisms. They seek to answer the question: What can and should be done to confront salient issues of the global problematic ? More specifically, the essayists ask whether currently existing multilateral mechanisms are up to the challenge.